2006
DOI: 10.1080/00016480600606681
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anatomic variations of paranasal sinuses and chronic sinusitis in children

Abstract: The maxillary sinus was the most commonly involved sinus, followed by the ethmoid, sphenoid, and frontal sinuses. There was no relationship between age and severity of sinusitis. Agger nasi cell was the most common anatomical variation, followed by septal deviation, Haller cell, concha bullosa, paradoxical middle turbinate, and Onodi cell. The prevalence of septal deviation increased with age. There was no significant relationship between the sinusitis and anatomic variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…Our data found 16 (12.3%) cases of this anomaly: nine (6.9%) on the right, four (3.1%) on the left, and three (2.3%) identified bilaterally. These results are very close to other studies, which reported from 11% to 14.3% cases [7,9,[11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…Our data found 16 (12.3%) cases of this anomaly: nine (6.9%) on the right, four (3.1%) on the left, and three (2.3%) identified bilaterally. These results are very close to other studies, which reported from 11% to 14.3% cases [7,9,[11][12][13].…”
Section: Discussionsupporting
confidence: 92%
“…This could be explained by the critical location of Haller cells immediately lateral to the maxillary infundibulum which can interfere with the normal drainage of the maxillary sinus. Several investigators have also come to the same conclusion regarding the association between the presence of Haller cells and maxillary sinusitis [ 23 - 25 ]; on the other hand, some authors believe that only medium and large sized Haller cells can lead to mucosal thickening of the maxillary sinus [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 96%
“…However, previous studies indicate no major anatomic predisposing factors for rhinosinusitis, which made this an unlikely issue. 16,17 Also, these distances were measured on two-dimensional CT images, and if these were not true axial and coronal planes, then measurements would be slightly off. To minimize this possibility, CTs with direct thin-cut (≤1 mm) axial acquisition protocols were used and the nasal floor was used to confirm the true nature of the axial plane.…”
Section: Discussionmentioning
confidence: 99%